Design and implementation of multi-mode variable bit-rate modulator and high bit-rate demodulator for low earth orbit satellites - Tai, Wei Chua (2008)
This research considers the design and implementation of an L and S-Band re-configurable communication payload (Merlion) that is to be flown on the UoSAT-12 LEO mini-satellite during 1999. The payload is intended to serve as a space-bome communication test-bed that would allow experimentation on propagation effects and a number of coding and modulation schemes besides providing for real-time as well as store and forward communications.